Endovascular Treatment of Intracranial Atherosclerotic Stenosis: Current Debates and Future Prospects - Luo, Jichang; Wang, Tao; Gao, Peng; Krings, Timo; Jiao, Liqun (Frontiers in Neurology, 2018)
Intracranial atherosclerotic stenosis (ICAS) is a common cause of transient ischemic attack (TIA) and ischemic stroke. Endovascular treatment, including balloon angioplasty alone, balloon-mounted stents, and self-expandable stent placement with or without prior angioplasty, is an alternative to medical treatment for the prevention of recurrent TIA or ischemic stroke in patients with ICAS. Although the SAMMPRIS and VISSIT trials supported medical management alone against endovascular treatments, both randomized controlled trials were criticized due to flaws relating to patient-, intervention-, and operator-related factors. In this review, we discuss the current debate regarding these aspects and suggest approaches to solve current controversies in the future. In our opinion, endovascular treatment in carefully selected patients, individualized choice of endovascular treatment subtypes, and an experienced multidisciplinary team managing the patient in the pre-, peri- and post procedural period have the potential to provide safe and efficious treatment of patients with symptomatic ICAS.